(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is dedicated to getting to know a book, reading, and giving a special pleasure to a person. Reading a book directs a person directly to practice, to harmony with life, to receive spiritual benefits.